PERKEMBANGAN PELAKSANAAN PEMILIHAN UMUM KEPALA DAERAH LANGSUNG DAN SERENTAK DALAM RANGKA PENGUATAN DEMOKRASI LOKAL DALAM PERSPEKTIF KETATANEGARAAN INDONESIA - Mz, H. Ismail (Fakultas Hukum Universitas Nahdlatul Wathan Mataram, 2020)
The simultaneous regional head elections have a very close correlation with the implementation of people's sovereignty. This is in accordance with the mandate of Article 1 paragraph (2) of the 1945 Amendment, explaining that